Integrated intelligent water-energy metering systems and informatics: Visioning a digital multi-utility service provider. (July 2018) - Stewart, Rodney A.; Nguyen, Khoi; Beal, Cara; Zhang, Hong; Sahin, Oz; Bertone, Edoardo; Vieira, Abel Silva; Castelletti, Andrea; Cominola, Andrea; Giuliani, Matteo; Giurco, Damien; Blumenstein, Michael; et al.
Abstract: Advanced metering technologies coupled with informatics creates an opportunity to form digital multi-utility service providers. These providers will be able to concurrently collect a customers' medium-high resolution water, electricity and gas demand data and provide user-friendly platforms to feed this information back to customers and supply/distribution utility organisations. Providers that can install low-cost integrative systems will reap the benefits of derived operational synergies and access to mass markets not bounded by historical city, state or country limits. This paper provides a vision of the required transformative process and features of an integrated multi-utility service provider covering the system architecture, opportunities and benefits, impediments and strategies, and business opportunities. The heart of the paper is focused on demonstrating data modelling processes and informatics opportunities for contemporaneously collected demand data, through illustrative examples and four informative water-energy nexus case studies. Finally, the paper provides an overview of the transformative R&D priorities to realise the vision. Highlights: Vision of an integrated digital multi-utility provider. Benefits, opportunities and impediments to a digital multi-utility service provider. Examples and case studies demonstrating contemporaneous water-energy nexus modelling. Research and development priorities for digital multi-utility transformation.